Eco Landscape For War Devastation Area In Tripoli-Libya (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Ecological Landscape is a method of organizingthe building's and maintaining the ground landscaping thatconsiders the ecology of the site creates gardens and parksthat enhance the surrounding landscape for the benefit ofhumans and all other organisms' life in the ecosystem. Therefore, to build an eco-landscape and sustainable urbandesign, these challenges need to be faced with efficient andcreative ideas and hard efforts to succeed. The paper focuseson the environmental issues, investigates and works onthe development of old military sites and camps, which isdestroyed by the 2011 war in Tripoli, to re- functioning anddeveloping them as entertaining places and open publicgreen spaces for people. Therefore, these sites have beentaken as a case study of the paper, to integrate them withinthe urban land use planning of the city of Tripoli, consideringthe idea of eco-sustainable landscape architecture of theurban built environment of the city. This could create solutionsfor the problem of the lack of open green public spaces andplaces in the cityof Tripoli.